PERLINDUNGAN HUKUM TERHADAP PENUMPANG DAN BARANG MILIK PENUMPANG DALAM JASA PENGANGKUTAN UDARA - Pasaribu, Mangara (JURNAL MERCATORIA, 2016)
The arrangements regarding the legal protection of passengers and goods on the transport of air, is set out in legislation, agreements, and habits. The air transport law is keperdataan, the provision of air transport to be found in the laws of positive air in Indonesia are: Air Transportation Ordinance Stbl. 1939 No. 100, law No. 1 of 2009, and the Statute No. 8 1999. The responsibility of carrying on the safety of passengers and goods in the implementation of air transportation The principle of presumption of liability /presumtion of/ presumtion fault of negligence. The carrier is responsible for loss suffered by passengers or goods because the sender of a passenger wounded or killed, his baggage or damaged or lost, or damage to goods transfers and the delay in coming, while the principle of limitation of liability. The responsibility of the carrier is limited to a certain amount, this principle which encourages the carrier to resolve the problem by peaceful means. And the principle of absolute liability or strict liability. The carrier is considered to be always responsible without any possibility of freeing themselves unless the aggrieved innocent or were responsible for the losses on him. Compensation given by air carriers is a number of nominal value of money as a form of responsibility for accidents that caused deaths or injuries, lost baggage and flight delays. Legal efforts for passenger who feel or losses can file a lawsuit or claim to the airline, lawsuit or dispute settlement can be reached through two channels, namely the courts and lanes outside the court.